2020
DOI: 10.31814/stce.nuce2020-14(3)-08
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fiber size on mechanical properties of strain-hardening fiber-reinforced concrete

Abstract: This research deals with the influences of macro, meso and micro steel-smooth fibers on tensile and compressive properties of strain-hardening fiber-reinforced concretes (SFCs). The different sizes, indicated by length/diameter ratio, of steel-smooth fiber added in plain matrix (Pl) were as follows: 30/0.3 for the macro (Ma), 19/0.2 for the meso (Me) and 13/0.2 for the micro fiber (Mi). All SFCs were used the same fiber volume fraction of 1.5%. The compressive specimen was cylinder-shaped with diameter × heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…69,78 Studies on the reinforcement of concrete structures with aramid fibers (AF) have also been sought through, it should be noted that AF looses considerable strength in alkaline environments. [87][88][89] Moreover, AF tends to absorb water, which leads to a deterioration of fiber stiffness. 82,83 Nonetheless, progress is driven by research continuously.…”
Section: Fiber Materialsmentioning
confidence: 99%
“…69,78 Studies on the reinforcement of concrete structures with aramid fibers (AF) have also been sought through, it should be noted that AF looses considerable strength in alkaline environments. [87][88][89] Moreover, AF tends to absorb water, which leads to a deterioration of fiber stiffness. 82,83 Nonetheless, progress is driven by research continuously.…”
Section: Fiber Materialsmentioning
confidence: 99%
“…The fiber size and aspect ratio were reported to importantly affect the tensile behaviors of HPFRC [19,20]. The combination between short and long fibers could create the synergy effect on enhancing mechanical properties of HPFRC [13,21,22].…”
Section: Materials and Beam Preparationmentioning
confidence: 99%
“…Direct tensile strength of HPFRC was 9.81 MPa [13] 164 165 The fiber size and aspect ratio were reported to importantly affect the tensile 170 behaviors of HPFRC [19,20]. The combination between short and long fibers could 171 create the synergy effect on enhancing mechanical properties of HPFRC [13,21,22] 172 Hence, the HPFRC placed in beams were used hybrid fibers: long hooked fibers with 173 volume fraction of 1.0% and short smooth fibers with volume fraction of 0.5%.…”
mentioning
confidence: 99%
“…These characteristics related to the fiber-matrix interfacial bond strength. 11,12 Ferrara et al 13 stated that the tensile performance of HPFRC was highly affected by fiber orientation and distribution, while Zheng 14 indicated that the increase of tensile strength and elastic modulus of fibers correlated to the improved resistances of concrete. Besides, the micro fiber with its length less than 0.1 mm could be higher homogenous distributed and thus result the greater packing density of concrete.…”
Section: Introductionmentioning
confidence: 99%